Model Pengembangan Kompetensi bagi Auditor Perbankan Syariah di Indonesia - Simarmata, Harianto (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
The development of competence for Sharia banking auditors is a crucial factor in ensuring audit quality and compliance with Sharia principles. This research seeks to explore and design a competency development model for Sharia banking auditors in Indonesia through an extensive review of existing literature. The study employs a qualitative method with a literature review approach, encompassing an analysis of various academic sources, regulations, and best practices in Sharia auditing. The findings indicate that the KSOC (Knowledge , Skill , and Other Characteristics) model is an effective approach for developing the competence of Sharia banking auditors. This model comprises three key aspects: Knowledge , which includes mastery of Sharia principles and regulations; Skill , which involves enhancing technical audit capabilities; and Other Characteristics, which emphasize strengthening ethics and professionalism. The findings suggest that optimal auditor competence development should integrate continuous education, certification training, and practical experience in the Sharia banking sector. This study concludes that a systematic approach based on the KSOC model can enhance audit effectiveness and strengthen public trust in the Sharia banking industry in Indonesia.